2018
DOI: 10.1016/j.contraception.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and correlates of contraception among postpartum women in Kenya: results from a national cross-sectional survey

Abstract: Objectives To characterize uptake and correlates of effective contraceptive use postpartum. Study Design We analyzed data from a national, cross-sectional evaluation of prevention of mother-to-child HIV transmission programs that enrolled women attending 6-week or 9-month infant immunization visits at 120 Kenyan maternal and child health clinics. We classified women who resumed sexual activity postpartum and did not desire a child within 2 years as having a need for family planning (FP). Results We include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 20 publications
7
16
1
Order By: Relevance
“…The major reasons for not currently using contraceptives were feeling of not exposed to the risk of pregnancy due to amenorrhea after birth 48(29 %), followed by were feeling of not exposed to the risk of pregnancy due to breastfeeding 36(22%) and partner opposed to use family planning 28(17%) (Figure2). This finding is in line with a study conducted in Kenya (59%) [16]. This similarity might be due to similar socio-demographic characteristics.…”
Section: Reasons For Not Using Contraceptive Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…The major reasons for not currently using contraceptives were feeling of not exposed to the risk of pregnancy due to amenorrhea after birth 48(29 %), followed by were feeling of not exposed to the risk of pregnancy due to breastfeeding 36(22%) and partner opposed to use family planning 28(17%) (Figure2). This finding is in line with a study conducted in Kenya (59%) [16]. This similarity might be due to similar socio-demographic characteristics.…”
Section: Reasons For Not Using Contraceptive Methodssupporting
confidence: 92%
“…This might be due to women who were proper counseled about available methods of family planning and the consequences of frequent birth during ANC by providers. However, a study done in Kenya shows that discussing FP in ANC alone was not associated with effective contraceptive use [16].…”
Section: Bivariate and Multivariate Analysis Of Factors Associated Wimentioning
confidence: 99%
“…Lastly, in this meta-analysis, we observed that those mothers who had ANC and PNC follow-up were more likely to use contraceptive as compared to their counterparts, respectively. This finding is supported by previous studies conducted in Kenya [55], Uganda [48], Rwanda [52], and America [64]. These studies reported that having antenatal as well as postnatal care services were positively associated with contraceptive uses.…”
supporting
confidence: 86%
“…Similarly, those mothers whose postpartum epoch was six months and above after childbirth were more likely to use family planning as compared to those mothers whose postpartum epoch was less than six months after childbirth. This finding is supported by previous studies conducted in Kenya [55] and Ethiopia [28]. This might be due to the fact that as the duration of the postpartum period increases, mothers engage in sexual activity, and moreover, their menses will resume.…”
supporting
confidence: 86%
See 1 more Smart Citation